2014
DOI: 10.1016/j.jinorgbio.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial and antibiofilm activities of copper(II) complexes

Abstract: Gram-positive and Gram-negative bacteria, albeit that activity was generally higher for the former. The antibiofilm activity was then determined against a clinical isolate of meticillin-resistant Staphylococcus aureus (MRSA). Strikingly, the copper complexes tested showed significant activity against biofilms, and were better in the removal of biofilms than vancomycin, an antibiotic that is currently used in the treatment of MRSA infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…125 Copper 353 on the other hand, is reported to enhance bacterial aggregation at toxic levels, which is 354 thought to act as protective responses to stress. 126,127 Presence of copper in drinking water 355 has also been shown to induce VBNC state on the opportunistic pathogen P. aeruginosa. Decreasing temperatures from 37°C to 25°C or 15°C were found to elevate the intracellular 415 c-di-GMP level in the pathogenic V. cholerae, in turn, enhancing biofilm growth.…”
Section: (Based 340mentioning
confidence: 99%
“…125 Copper 353 on the other hand, is reported to enhance bacterial aggregation at toxic levels, which is 354 thought to act as protective responses to stress. 126,127 Presence of copper in drinking water 355 has also been shown to induce VBNC state on the opportunistic pathogen P. aeruginosa. Decreasing temperatures from 37°C to 25°C or 15°C were found to elevate the intracellular 415 c-di-GMP level in the pathogenic V. cholerae, in turn, enhancing biofilm growth.…”
Section: (Based 340mentioning
confidence: 99%
“…[1][2][3][4][5], antibacterial (Ag, Au, Hg, Fe, Cu, etc.) [1,2,6] and antiviral activities (Co, V, etc.) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Cu 2? complex also demonstrated good antimicrobial properties (Beeton et al 2014), however, copper nanoparticles have been demonstrated to possess higher antimicrobial activities than the equivalent amount of copper containing compounds such as CuCl 2 because copper nanoparticles have larger surface to volume ratio, crystalline structure. The more reactive sites of copper nanoparticles therefore could produce more reactive oxygen species (ROS) that could result in considerable lipid peroxidation, protein oxidation and DNA degradation and finally killing the cells (Rai et al 2009;Chatterjee et al 2014).…”
Section: Resultsmentioning
confidence: 99%